PENGARUH CITRA MEREK, ONLINE CUSTOMER REVIEW, DAN RATING TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI SHOPEE DI SOLO - Nerissa Arviana Dewi; Sudarwati Sudarwati; Supawi Pawenang (Jurnal AKTUAL, 2022)
Shopee is one of the marketplaces that is being intensively used among the public. Many parties take advantage of online business opportunities by enlivening the existing mobile marketplace segment. This study aims to examine the brand image, online customer reviews, and ratings on purchasing decisions on the Shopee application in Solo. Data collection techniques used in the study were observation and distributing questionnaires to Shopee application customers in Solo. The research sample was purposive sampling as many as 100 respondents with a multiple linear regression method. Data analysis techniques in this study include several data preparations, validity test, multiple linear regression hypothesis testing, f test, t-test, and determination test. The results showed that brand image, online customer review, and rating simultaneously had a significant effect on purchasing decisions on the Shopee application in Solo. Purchase decisions can be explained by brand image, online customer review, and rating of 71.9%, and the remaining 28.1% is explained by other variables such as price, promotion, product quality, and so on which were not examined in this study.